(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This essay demonstrates that the validation of prior learning (VPL) is more than a procedural mechanism for recognizing informal and nonformal learning; it is deeply embedded in socio-political and epistemic frameworks, shaped by ideological assumptions about society, education, and knowledge. Drawing on Breier’s (2005) tripartite framework—market, liberal, and critical perspectives—the author explores how different visions of VPL are linked to broader socio-political goals, from workforce development to social equity to institutional transformation. Furthermore, the paper contends that VPL requires a robust epistemological foundation, asking not only whether claims to know are socially and politically compelling, but also whether they are rooted in differing bases of justification and can be said to be true. In this way, VPL practice might validate claims to knowledge, but might also validate the justification of that knowledge and its truth status, thus pointing to the challenge of achieving both access and rigor in higher education.